Reaching the malaria elimination goal in Brazil: a spatial analysis and time-series study - Gabriel Zorello Laporta; Maria Eugenia Grillet; Sheila Rodrigues Rodovalho; Eduardo Massad; Maria Anice Mureb Sallum (BMC, 2022)
Abstract Background Since 2015, the Global Technical Strategy (GTS) for Malaria 2016-2030 has been adopted by the World Health Organization (WHO) as a comprehensive framework to accelerate progress for malaria elimination in endemic countries. This strategy sets the target of reducing global malaria incidence and mortality rates by 90% in 2030. Here it is sought to evaluate Brazil's achievements towards reaching the WHO GTS milestone in 2030. Considering the total number of new malaria cases in 2015, the main research question is: will Brazil reach the malaria elimination goal in 2030? Methods Analytical strategies were undertaken using the SIVEP-malaria official databases of the Brazilian Malaria Control Programme for the Brazilian Amazon region from 2009 to 2020. Spatial and time-series analyses were applied for identifying municipalities that support the highest numbers of malaria cases over the years. Forecast analysis was used for predicting the estimated number of new cases in Brazil in 2025-2050. Results Brazil has significantly reduced the number of new malaria cases in 2020 in comparison with 2015 in the states of Acre (− 56%), Amapá (− 75%), and Amazonas (− 21%); however, they increased in the states of Pará (156%), Rondônia (74%), and Roraima (362%). Forecast of the predicted number of new malaria cases in 2030 is 74,764 (95% CI: 41,116-141,160) in the Brazilian Amazon. Conclusions It is likely that Brazil will reduce the number of new malaria cases in the Brazilian Amazon in 2030 in relation to that in 2015. Herein forecast shows a reduction by 46% (74,754 in 2030 forecast/137,982 in 2015), but this reduction is yet far from the proposed reduction under the WHO GTS 2030 milestone (90%). Stable and unbeatable transmission in the Juruá River Valley, Manaus, and Lábrea still support endemic malaria in the Brazilian Amazon. Today's cross-border malaria is impacting the state of Roraima unprecedently. If this situation is maintained, the malaria elimination goal (zero cases) may not be reached before 2050. An enhanced political commitment is vital to ensure optimal public health intervention designs in the post-2030 milestones for malaria elimination. Graphical Abstract